POTENSI AI DALAM PEMBELAJARAN INKLUSIF DI PENDIDIKAN DASAR: Kecerdasan Artifisial, Pendidikan Dasar, Pendidikan Inklusif, Siswa Berkebutuhan Khusus, Teknologi Pendidikan - Wahyudi Ariannor (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2025)
Abstract: This article explores the potential application of artificial intelligence (AI) in supporting inclusive education at the primary school level. The study employs a literature review method with a descriptive-qualitative approach, analyzing relevant scholarly articles published between 2019 and 2025. The findings reveal that AI plays a strategic role in creating adaptive, personalized, and responsive learning environments, particularly for students with special needs. Technologies such as recommendation systems, learning robots, and voice- and text-based platforms are found to be effective in enhancing accessibility and participation in learning. However, the implementation of AI also faces several challenges, including limited infrastructure, low digital literacy among teachers, and the lack of supportive policies. This review recommends continuous teacher training, the development of inclusive policies, and cross-sector collaboration to optimize the use of AI in inclusive primary education. Keywords: artificial intelligence, primary education, inclusive education, special needs students, educational technology